The History And Values of Tolerance In Tabot Traditional Ceremonies In Bengkulu Society (History Department, Semarang State University and Historian Society of Indonesia, 2020)
This article aims to reveal the history of the Tabot tradition and the values of tolerance contained in the Tabot celebration in each month of Muharram in the Bengkulu Society. This research method uses qualitative and history methods, with data collection through documents, interviews, and observations to the perpetrators of the Tabot, traditional leaders, and the community around the Tabot event in Bengkulu. The results of this study indicate that; First, the Tabot tradition is related to the growth and development of Islam in Bengkulu, which was developed by a Shiite Islamic cleric from southern India named Syeh Burhanuddin who was later better known as Imam Senggolo, namely in the 18th century. He introduced the procedures of the Tabot ceremony to the people of Bengkulu, who then passed on to their descendants who assimilated with the people of Bengkulu. Secondly, the values of tolerance in the tabot ceremony every month in Muharram in Bengkulu include mutual respect, mutual respect, help, and cooperation. This is evidenced in the Tabot ceremony activities open to the public so that all people can follow it and do not side with a particular religion, ethnicity, and culture of a particular community, but embrace all the differences that exist. Tabot tradition activities are not only as a religious activity but also are expected to reduce the division of society and also non-Muslims in the city of Bengkulu.Artikel ini bertujuan untuk mengungkap sejarah tradisi Tabot dan nilai-nilai toleransi yang terkandung di dalamnya di setiap bulan Muharram di Masyarakat Bengkulu. Metode penelitian ini menggunakan metode kualitatif dan sejarah, dengan pengumpulan data melalui dokumen, wawancara, dan observasi terhadap para pelaku Tabot, tokoh adat, dan masyarakat di Bengkulu. Hasil penelitian menunjukkan bahwa; Pertama, tradisi Tabot terkait dengan tumbuh kembang Islam di Bengkulu yang dikembangkan oleh seorang ulama Islam Syiah dari India selatan bernama Syeh Burhanuddin yang kemudian lebih dikenal dengan nama Imam Senggolo, pada abad ke-18. Ia memperkenalkan tata cara upacara Tabot kepada masyarakat Bengkulu, yang kemudian diwariskan kepada keturunannya yang berasimilasi dengan masyarakat Bengkulu. Kedua, nilai-nilai toleransi dalam upacara tabot setiap bulan Muharram di Bengkulu meliputi saling menghormati, saling menghormati, membantu, dan gotong royong. Hal tersebut dibuktikan dalam kegiatan Upacara Tabot yang terbuka untuk umum sehingga semua masyarakat dapat mengikutinya dan tidak berpihak pada agama, suku, dan budaya tertentu dari masyarakat tertentu, melainkan merangkul segala perbedaan yang ada. Kegiatan tradisi tabot tidak hanya sebagai kegiatan keagamaan tetapi juga diharapkan dapat mengurangi perpecahan masyarakat dan juga nonmuslim yang ada di kota Bengkulu.Â